The Influence of Teacher Well-Being and Work Environment on Work Motivation: : A Systematic Literature Review - Anggun Dwi Damayanti; Desi Isna Hernayanti; Dwi Widiyono; Uswatun Kasanah; Eko Santoso; Dian Rohadhona Wulandari; Kristiani; Ngurah Ayu Nyoman (Elementary Education Journal, 2026)
Teacher work motivation plays a crucial role in determining the quality of education, as it is closely associated with teachers’ performance, commitment, and engagement in the learning process. However, teacher motivation is influenced by various factors, particularly teacher well-being and work environment, which are often examined separately in previous studies. Therefore, this study aims to analyze and synthesize the relationships among teacher well-being, work environment, and teacher work motivation through a Systematic Literature Review (SLR) approach. This study employed the PRISMA guidelines to systematically identify, screen, and select relevant articles from databases such as Scopus, ScienceDirect, Google Scholar, and Garuda. A total of 36 scientific articles that met the inclusion criteria were analyzed. The findings indicate that teacher well-being is a multidimensional construct encompassing financial, psychological, social, and professional aspects, while the work environment includes organizational, social, and physical dimensions that shape teachers’ work experiences. Furthermore, both teacher well-being and work environment are found to have significant direct and indirect effects on teacher work motivation, often mediated by variables such as job satisfaction and organizational commitment. The results also reveal that the relationships among these variables are complex and interconnected, suggesting that teacher motivation cannot be understood in isolation. This study concludes that improving teacher work motivation requires an integrated approach through the enhancement of teacher well-being and the creation of a supportive work environment. The findings provide both theoretical contributions to educational management literature and practical implications for policymakers and school leaders in improving educational quality.